Highly selective high-speed circularly polarized photodiodes based on π-conjugated polymers - Ward,MD; Wade,J; Shi,X; Nelson,J; Campbell,AJ; Fuchter,MJ (Advanced Optical Materials, 2022)
Chiral π-conjugated molecular systems that are intrinsically sensitive to the handedness of circularly polarized (CP) light potentially allow for miniaturized, low-cost CP detection devices. Such devices promise to transform several technologies, including biosensing, quantum optics, and communication of data encrypted by exploiting the spin angular momentum of light. Here a simple, bilayer organic photodiode (CP OPD) comprising an achiral π-conjugated polymer–chiral additive blend as the electron donor layer and an achiral C60 electron acceptor layer is realized. These devices exhibit considerable photocurrent dissymmetry gph, with absolute values as high as 0.85 and dark currents as low as 10 pA. Impressively, they showcase a linear dynamic range of 80 dB, and rise and fall times of ≈7 µs, which significantly outperforms all previously reported CP selective photodetectors. Mechanistically, it is shown that the gph is sensitive to the thickness of both the chiral donor and achiral acceptor layers and that a trade-off exists between the external quantum efficiency and gph. The fast-switching speeds of these devices, coupled with their large dynamic range and highly selective response to CP light, opens up the possibility of their direct application in CP sensing and optical communications.